![3x {}^{2} + 6x +3 = 0 3x {}^{2} + 6x +3 = 0](https://tex.z-dn.net/?f=3x+%7B%7D%5E%7B2%7D+%2B+6x+%2B3+%3D+0++)
Soluções para a tarefa
Respondido por
1
3x² + 6x + 3 = 0. ====> :(3)
x² + 2x + 1 = 0
(x +1)² = 0
x + 1 = 0
x = -1
Respondido por
0
Resposta:
x1 = -1 >>>
x2 = -1 >>>
Explicação passo-a-passo:
3x² + 6x + 3 = 0 por 3
x² + 2x + 1 = 0
trinômio quadrado perfeito . acha as raizes fatorando pela regra
[ Vx² + V1 ]² = ( x + 1 )² ou ( x + 1 ) ( x + 1 ) = 0
x + 1 = 0
x = -1 >>>>
x + 1 = 0
x = -1 >>>>>
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás